The Impact of Social Media Use on Adolescent Mental Health - Muhammad Syahruzzidan As Syauqi; Pepin Nahariani (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Information and Communication Technology has developed extremely rapidly, especially for social media. Such development can lead to increased dependence on electronic devices influencing adolescent mental health. The purpose of the study was to analyze the relationship between social media usage and adolescent mental health in SMP Negeri 2 Jombang. In this study, the correlation analytic quantitative research design with the cross-sectional approach was utilized. There were 320 in total students, and 76 students were the sample by the cluster random sampling technique. Statistical tests were performed by Spearman's Rank. There were 57.9% students who experienced mild social media addiction. Simultaneously, 38.2% of students experienced mild depressive symptoms. The Spearman's Rank statistical test analysis findings revealed (ρ) = 0.000 < (α) 0.05, which confirms that teen mental health is correlated with social media use. The value of r is 0.402, and the level of correlation is moderate. Social media use and teen health were related as the more frequently one used social media, the greater the possibilities that they would be affected by seeing others' success, bodies, and lifestyles and become possible stressors leading to depression or mental illnesses. Preventive and promotive measures were needed for the early detection of mental disorders in adolescents to avert more complex mental health problems.